A Study On Passport To The World 1 Textbook Based On School Level - Based Curriculum - Puspitasari, Khotimah Ermawati; , Drs. Djoko Srijono, M.Hum; , Aryati Prasetyarini, S. Pd, M. Pd (2013)
The study aims at describing whether or not themes and English materials on Passport to the World 1 textbook for grade VII of Junior High School are suitable with themes and indicators of English skills in School Level-based Curriculum. This research is content analysis research. In collecting the data, the writer uses document to collect the data. The data were analyzed by the steps follows: (1) the writer reads the data and finds out the data, (2) the writer measures the data whether the data is suitable or not with themes and indicators in School Levelbased Curriculum, (3) the writer makes an interpretation of the analysis. Based on the analysis, the writer can make some conclusion. First, themes in "Passport to the World 1" textbook are fair based on curriculum. The percentage of suitability is 42,85%. Second, listening materials are good based on curriculum and the percentage is 65,00%. Third, speaking materials are good based on curriculum and the percentage is 65,00%. Fourth, reading materials are good based on curriculum and the percentage is 72,72%. Fifth, The suitability of writing materials are good based on curriculum and the percentage is 63,63%. Therefore, themes and all of the language materials in textbook are good based on School Level-based Curriculum. The percentage of the suitability is about 63,76%. The result of the research shows that "Passport to the World 1" textbook for grade VII of Junior High School is good for developing students' ability to achieve the goal of learning English especially in developing the listening, speaking, and reading skill. The materials of writing are poor than the other skill materials for students grade VII, so it needs the other writing materials to support the writing lesson.